Is the use of contraceptives associated with periodontal diseases? A systematic review and meta-analyses - Micaele Maria Lopes Castro; Maria Karolina Martins Ferreira; Iasmin Encaua Essashika Prazeres; Paula Beatriz de Oliveira Nunes; Marcela Baraúna Magno; Cassiano Kuchenbecker Rösing; Lucianne Cople Maia; Rafael Rodrigues Lima (BMC, 2021)
Abstract Background Previous studies indicated an impact of hormonal contraceptive use on oral health. This systematic review aimed to investigate the evidence supporting the impact of the use of hormonal contraceptives and periodontal diseases. Methods This study is based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and based on the PECO acrostic. Inclusion criteria comprised observational studies including women (P), which evaluated hormonal contraceptive users (E) and hormonal contraceptive non-users (C), to verify the association between this hormonal therapy and the periodontal diseases (O). Searches were performed on 5 databases: PubMed, Scopus, Web of Science, Cochrane Library, LILACS and grey literature (OpenGrey and Google Scholar). After the selection process, the included studies were evaluated qualitatively. Moreover, quantitative data were analyzed in two meta-analyses for clinical attachment loss (CAL) and probing depth (PD). Finally, the level of certainty was measured with the GRADE (Grading of Recommendations Assessment, Development, and Evaluation) tool between periodontal clinical parameters. Results 18 articles were eligible for the qualitative synthesis and 7 of them were selected for quantitative analysis. Hence, 15 of the eligible articles reported an association between the use of hormonal contraceptives and severity of periodontal disease. However, 6 articles demonstrated high risk of bias and were excluded from quantitative synthesis. The meta-analysis showed a statistically significant difference for CAL (MD 0.24 [0.09, 0.40]; p = 0.002), but in PD (MD 0.05 [− 0.05, 0.15]; p = 0.33) such difference was not identified. A very low level of evidence was found between the clinical parameters. Conclusions The use of hormonal contraceptives may be associated to severity of periodontal diseases. However, the quantitative analysis points to an inconclusive outcome due to the high level of heterogeneity. The association is biologically plausible, however additional studies are warranted to better elucidate the clinical significance of this possible association.